Bactérias diazotróficas endofíticas em cultivares de milho em áreas de cerrado e mata no Estado de Roraima - Gomes, Maria de Lourdes (2009)
Maize plants associate with diazotrophic bacteria and can be benefitted by Biological Nitrogen Fixation - BNF, however these microorganisms present some variations in relation to the vegetal genotypes and environment where are isolated. The aim of this study was structure a collection of endophytic diazotrophic bacterias as well as characterize the density and diversity of the bacterias in four maize genotypes (varieties BRS 4157, BR 106 and hybrids BRS 1010 and BRS 3030), cultivated in cerrado and altered forest area in Roraima, with and without application of nitrogen fertilizer. The endophytic bacterias were isolated and phenotypically characterized in DYG'S solid culture medium and inoculated in BMGM semi-solid culture medium to evaluate nitrogen fixation capacity. The endophytic diazotrophic bacterias were later characterized in semi-selective culture medium JMV, LGI and NFb (3x) together with bacterias used as references: HRC54 (Herbaspirillum seropedicae), CBAmC (Azospirillum amazonense), Ppe8 (Burkholderia tropica), M130 (Burkholderia kururiensis) e Sp7 (Azospirillum brasilense). These bacterias were clustered using Simple Matching similarity index and the diversity was evaluated by the Shannon- Weaver index. A total of 537 endophytic bacterias isolated were obtained, and 55 presented BNF capacity. The population of diazotrophic bacterias ranged from 0.83 to 10.8 x 103 cells g-1 of the root and it presented in a maximum of 0.83 cells g-1 of the vegetable stem. Besides, so much the diazotrophic bacterias percentage in relation to the total number of endophytic bacterias, as well as the number of diazotrophic bacterias isolated, reflected an interaction among the maize cultivars and environments. Twelve phenotypic groups were verified with 85% of similarity among the bacterias, and few isolated were similar to the references strains. The bacterias clustered in relation to maize cultivars and environment where were isolated and, the presence of nitrogen did not interfered in the bacterias clustering. The presence of nitrogen increased the bacterias density in cerrado area that was the environment which presented smaller soil organic matter content. It was also observed larger diversity of bacterias in forest area in relation to the cerrado and in the maize varieties in comparison to the hybrids.